THE USE OF A READING CORNER IN INSTILLING THE STUDENTS READING INTEREST - Rahmawati, Lestari Nur; Abduh, Muhammad (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
Reading interests are very important to have mainly on students. Reading interests can come through support or without support is from inside someone's own heart. Student reading interests need to be resurrected from the age of elementary school, Surely the support and effort of teachers is essential in instilling reading interests. The research uses a type of qualitative research with case study designs. Data collection techniques use interviews, Observation and documentation. Data validity checks are performed through the source triangulation and engineering triangulation process. The data that's been obtained then reduced, presented, and the conclusion of the research suggests that the utilization of the reading corners in the SDN 1 Kemasan Sawit. In instilling an interest in reading is the use of teachers to make it easier for students to engage in literatory activities inside the classroom, is used for discussing and searching for material reference material students as well as for filling free time or during empty hours at class lesson in class. The management of the reading corner is done through four stages of planning, setting on motion, management and evaluation.